Development of Instructional Media Using 'Canva' Based on Animated Videos for the Subject of Biology - Ainil Fitri; Firdaus Annas; Liza Efriyanti; Gusnita Darmawati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Instructional media are essential for effectively conveying teaching materials to students. However, if the media used remain traditional and uninteresting, the teacher's delivery of the material may not reach students optimally. At SMAN N 1 Harau, the use of media in biology subjects only involves slides containing explanatory text narratives, leading to students encountering difficulties in comprehending the material quickly. This paper aims to create a valid, practical, and effective design for animated video-based media for biology subjects using Canva at SMA Negeri 1 Harau. The method employed is Research and Development (R&D) in the 4D version, which encompasses defining, designing, developing, and disseminating. The findings of this research were derived from product testing, including a validity test stage conducted by 3 experts, yielding a score of 0.79 in the valid category. Additionally, a practicality test was administered by 6 practitioners, resulting in a score of 0.88 in the very high category. Furthermore, an effectiveness test was conducted with 15 assessors, achieving a score of 0.65 in the effective category. In conclusion, instructional media designed based on animated videos proves to be practical and effective.Media pembelajaran sangatlah diperlukan untuk menyampaikan materi ajar pada peserta didik. Namun jika media yang digunakan masih tradisional dan tidak menarik mengakibatkan materi ajar yang disampaikan guru tidak sampai kepada siswa dengan maksimal. Penggunaan media pada mata pelajaran biologi di SMAN N 1 Harau hanya menggunakan slide yang berisikan narasi penjelasan berupa teks, sehingga siswa mengalami kendala dalam memahami materi dengan cepat. Tujuan dari tulisan ini untuk menghasilkan sebuah rancangan media berbasis video animasi pada mata pelajaran biologi menggunakan Canva di SMA Negeri 1 Harau yang valid, praktis dan efektif . Metode yang digunakan adalah Research and Development (R&D) versi 4D yaitu define, design, develop dan dissiminate. Temuan dari artikel ini didapatkan dari uji produk dengan tahapan uji validitas dari 3 orang ahli dengan nilai 0,79 kategori valid, uji praktikalitas dari 6 orang praktikalator dengan nilai 0,88 kategori sangat tinggi, dan uji efektivitas dari 15 orang penilai dengan nilai 0,65 kategori efektif. Dapat disimpulkan bahwa media pembelajaran yang diracangan berbasis video animasi dapat digunakan dengan valid praktis dan efektif.